Bitcoin: like a satellite or always hardcore? A core–satellite identification in the cryptocurrency market - Christoph J. Börner; Ingo Hoffmann; Jonas Krettek; Tim Schmitz (Journal of Asset Management, 2022)
Cryptocurrencies (CCs) have become increasingly interesting for institutional investors' strategic asset allocation and will therefore be a fixed component of professional portfolios in the future. However, this asset class differs from established assets primarily in that it has a higher standard deviation and tail risk. The question then arises whether CCs with similar statistical key figures exist. On this basis, a core market incorporating CCs with comparable properties enables the implementation of a tracking error approach. A prerequisite for this is the segmentation of the CC market into a core and a satellite, with the latter comprising the accumulation of the residual CCs remaining in the complement. Using a concrete example, we segment the CC market into these components based on modern methods from image/pattern recognition.
Keywords: C14; C46; C55; E22; G10; 330; Cryptocurrencies; Core–satellite identification; Market segmentation; Pattern recognition